Students’ Cognitive Perspective on The Implementation of Cooperative Learning in an Indonesian EFL Classroom - Fauziah, Nida; Hidayati, Arini Nurul; Dewi, Nita Sari Narulita; Abdulah, Fuad (Koli Journal : English Language Education, 2023)
Cooperative learning is a learning method in which students with different learning abilities are conditioned to work together in a group to achieve the same learning goals and maximize their learning process. This study aims to explore the cognitive perspectives of students in their experience when learning English in the classroom using the cooperative learning method. The data collection technique used was semi-structured interviews conducted on three students as participants in this study. The data was processed qualitatively using thematic analysis. The findings of this study indicate positive perspectives based on students' learning experiences using cooperative learning methods, namely; students are able to find partners who can support and increase the effectiveness in learning English and also the emergence of responsibilities in learning achievement.